Microstructure and properties of high alumina castables containing calcium alumino‐titanate. Issue 6 (15th May 2018) - Chen, Jianwei; Zhao, Huizhong; Zhang, Han; Li, Zhengkun; Zhang, Jiaqin
Abstract: Calcium alumino‐titanate (CAT)‐containing high alumina castables were prepared using bauxite, CAT, and α‐Al2 O3 as starting materials, and subsequently heat treated at various temperatures ranging from 1400°C to 1600°C. The thermo‐mechanical properties of the specimens as a function of the temperature were characterized in terms of linear shrinkage, bulk density, apparent porosity, cold crushing strength (CCS), modulus of rupture (MOR), residual ratio of MOR, and coefficient of thermal expansion (CTE). X‐ray diffraction (XRD) and scanning electron microscopy (SEM) were used to determine the phase composition and microstructural evolution, respectively. Sintering at temperatures between 1450 and 1500°C promoted normal grain growth, with the formation of a granular surface contact, and abnormal grain growth occurred at higher temperatures (≥ 1550°C). The cold strength of the specimen initially increased and subsequently decreased with temperature, whereas the residual ratio of MOR initially decreased with increasing temperature to 1550°C, then increased above 1550°C. In addition, the CTE of the specimen was only minimally influenced by the firing temperature.